Integrate Geospatial Data from Google Places API and OpenStreetMap for Gas Station Mapping in Hanoi, Vietnam - Viet Thanh, Nguyen; Anh Le, Hoang; Minh Phuong, Do (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Visualizing the spatial distribution of gas stations supports the assessment of service coverage, optimization of fuel supply, urban planning, and environmental impact control related to the emission of hazardous gases during fuel distribution. This study focuses on mapping the distribution of gas stations across Hanoi by integrating data from Google Places API and OpenStreetMap into a Geographic Information System (GIS). Using Python programming, data were collected, cleaned, and processed to determine the location, density, and spatial distribution of gas stations throughout the city. The results reveal that in 2024, Hanoi had a total of 382 gas stations, with an average density of 0.11 stations per km² and 0.05 stations per 1,000 inhabitants. The spatial distribution varies significantly between urban and suburban districts. This approach is scalable to other cities and provides a foundation for estimating vapor emissions and other pollutants generated during fuel distribution, contributing to improved energy management and sustainable development toward net-zero emissions in the future.